Circulating tumour cells and lung microvascular tumour cell retention in patients with metastatic breast and cervical cancer. Issue 2 (28th January 2015) - Peeters, Dieter J.E.; Brouwer, Anja; Van den Eynden, Gert G.; Rutten, Annemie; Onstenk, Wendy; Sieuwerts, Anieta M.; Van Laere, Steven J.; Huget, Philippe; Pauwels, Patrick; Peeters, Marc; Vermeulen, Peter B.; Dirix, Luc Y.
Highlights: Pulmonary microvascular obstruction with CTCs can be observed in some patients with metastatic breast and cervical cancer. We suggest that CTCs might have broader systemic effects beyond their significance as predictors of tumour progression. This study might provide a glimpse into some of the first steps that might be operative in the formation of metastases. Abstract: We have shown that in up to half of the patients with metastatic breast cancer (MBC), higher numbers of circulating tumour cells (CTCs) are present in the central venous blood (CVB) compared to the peripheral venous blood (PVB), suggesting that the lungs might retain a substantial number of CTCs. Here we report the presence of tumour cell emboli (TCE) in the microvasculature of the lungs in three out of eight patients with MBC and one patient with metastatic cervical carcinoma who had markedly elevated numbers of CTCs in the blood. All these patients suffered from symptomatic dyspnoea not easily attributable to other causes. No TCE were observed in five patients with MBC and elevated CTC counts and three patients with MBC who had low CTC counts (<5/7.5 ml). To investigate whether CTCs derived from CVB or PVB exhibit different transcriptional characteristics that might explain selective CTC retention, paired CTC samples from CVB and PVB of 12 patients with advanced breast cancer were subjected to gene expression analysis of 105 genes. No significant differences in CTC gene expression were observed. Together, these data suggest that potentially clinically relevant CTC retention in the microvasculature of the lung can occur in a subset of patients with advanced metastatic breast and cervical cancer, which seems to be transcriptionally non-selectively.